perancangan dan implementasi sistem pelaporan monitoring spektrum frekuensi radio - Eet Widarini; I Gede Pasek Suta Wijaya; Andy Hidayat Jatmika (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
Loka Monitor Spektrum Frekuensi Radio Mataram office is technical implementation unit is in the Directorate General of Resources and Post and Information. This unit is in charge to implementing the monitoring and control in the field of radio frequency spectrum. This includes monitoring activities consisted of observation frequency band, radio station fixed service / mobile, radio broadcasting and television broadcasting. Currently, the reporting of data processing for monitoring activities is still done manually. To search for any deviation either center frequency deviation, bandwidth deviation nor search for legality of a station so the data must be analyzed one by one. While for the report generation and monitoring data recapitulation that has been processed will be sorted, then be transferred to ROL format (Report Online) as a report to the central office. Therefore, required a system that can process data computerized in order to obtain information about deviations. And required a system that can create reports and monitoring activities recapitulation per point location, per day, per week, per month, per three months, per six months and per year. The system is built by using CodeIgniter framework with the programming language PHP and HTML. The system was developed with six stages : data collecting, literature study, system design, coding / implementation, testing and reporting. Based on the test results that have been done on reporting system that were tested on 6 respondents of employees and 30 informatics students with the average percentage of the answer is 90.65% it the proposed system is already running well according to user needs.